Guerra ao terror e terror à guerra: políticas e práticas antiterror, liberdade e o futuro das TIC`s - Pompéo, Wagner Augusto Hundertmarck (2015)
The present work intends on analyzing the collection of communications and general data employed by public as well as private actors sustained during times of war on terror . In that regard, the issue of this research consists on conceiving an approach to account for those actors responsibility Nation-States along with private companies, both of which, in the context of law s internationalization and aided by the new information and communications technologies, violate Human Rights while claiming them to constitute antiterrorism strategies and policies. Concerning the methodology, classified as phenomenological-hermeneutical, it proceeds with a critical analysis of the International Criminal Court, Regional Justice Systems, and corresponding bibliography, aiming to diagnose what led the war on terror policies to shift towards the antagonist sentiment of a terror of war . Drawn from conclusion, the observed deviation seems to derive from the violations acted upon by the United States of America and its National Security Agency (NSA) which, while maintaining the pseudo-argument of war on terror , tampered communications between not only its own citizens and chiefs of government but also the ones from allied great powers. In accordance with that, and further critics that permeate the International Criminal Court since its creation, accused of being an eminently political entity in its decisions, ineffective in regards to the absence of coercion elements for its determinations, and even lacking in suitable answers to matters of global interest such as terrorism, drug traffic, and new rights transgressions derived from the internet network a revision of the Rome Statute is proposed upon the purpose of, if not to establish new crimes, provide a more autonomous concept of crimes against humanity against the ones of common violence. To that extension, the war on terror has been confirming some human rights freedom of communication and expression, and the right to privacy are also passive to non-violent restrictions. Therefore, it seems imperative to promote the dilation of the concept of crimes against humanity, howbeit being a juridical category, with the purpose as to encompass clandestine or covert violations which, in turn, are consistently promoted by the previously mentioned actors, Nation-States and private companies, namely Facebook and Google that respectively explore the social medias market and web search engines, just as well as VASTec, AT&T, and Amesys, specialized in mass communications interception.